Twenty Years of Devolution in Scotland: the End of a British Party System? - Fiona Simpkins (Revue Française de Civilisation Britannique)
The geographical divides that characterised the outcome of the June 2016 European referendum, with a Remain majority in Scotland and Northern Ireland and a Leave majority in England and in Wales, are symptomatic of the increasingly divergent electoral results of the last two decades in each of the four UK nations. While the roots of divergent political patterns across the UK may lay in the 1960s and 1970s with the emergence of the nationalist parties in Scotland and Wales and the long decline of the Conservatives north of the border, we shall contend that the introduction of devolution to Scotland and Wales in 1999 had the most considerable impact on British party politics.